The mediating role of self-efficacy in the relationship between ICT competency and learning outcomes in Cambodian public universities - Nguon, Chanbopheak; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study examines the mediating role of self-efficacy in the relationship between Information and Communication Technology (ICT) competency and learning outcomes among students in Cambodian public higher education institutions. Grounded in Bandura’s social cognitive theory, the research investigates how students’ digital skills and confidence jointly influence academic success. A quantitative approach was adopted, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). From 384 distributed questionnaires, 326 valid responses were collected, resulting in an response rate of 84.9%. The measurement model demonstrated strong reliability and validity, with Cronbach’s alpha exceeding 0.90 and Average Variance Extracted (AVE) above 0.70. Discriminant validity was confirmed through the Fornell–Larcker criterion and the Heterotrait-Monotrait (HTMT) ratio. Structural model results indicate that ICT competency positively influences both learning outcomes (β = 0.300, p < 0.001) and self-efficacy (β = 0.270, p < 0.001). Additionally, self-efficacy showed a significant effect on learning outcomes (β = 0.341, p < 0.001) and mediated the relationship between ICT competency and learning outcomes (β = 0.092, p < 0.001). The model explained 25.8% of the variance in learning outcomes (R² = 0.258) and 7.4% in self-efficacy (R² = 0.074). These findings highlight self-efficacy as a crucial mechanism through which digital competencies enhance student performance, emphasizing the importance of integrated strategies that strengthen both ICT skills and learner confidence.